1416. Assessing the potential for interspecies transmission of Clostridioides difficile on dairy farms. (31st December 2020) - Redding, Laurel; Webb, Terry; Barnhart, Denise; Baker, Linda; Bender, Joseph; Kristula, Michaela; Kelly, Donna
Abstract: Background: Clostridioides difficile (CD) can cause severe colitis in humans and many species of animals. It is thought that farm animals could be a reservoir for CD and that farm workers could therefore be at increased risk of colonization and infection with CD. While pigs and swine farm workers have been shown to be colonized with identical clones of CD, the zoonotic transmission of CD from animals to people has not been definitively demonstrated, and no studies have examined whether dairy farm workers, who are generally in closer contact with animals than swine farmers, are at increased risk of being colonized or infected with CD. The aim of this study was to assess whether dairy calves and farm workers harbored genetically similar isolates of CD. Methods: First, we validated a glove-juice protocol to detect CD spores on the hands of farm workers. Volunteers' hands were inoculated with serially diluted suspensions of non-toxigenic CD organisms, and hand rinsates underwent broth enrichment and anaerobic culture. Second, we collected fecal samples from 5 randomly selected dairy calves (< 7 d of age) from each of 23 farms in southeastern Pennsylvania, northern Maryland, and Delaware. We focused specifically on dairy calves, as the prevalence of CD is highest in this age group. Third, using the glove-juice protocol, we collected hand rinsates from 38 dairy farm workers who work closely with calves. Only 4 of these workers were willing to submit fecal samples along with their hand rinsates. All fecal samples and hand rinsates underwent broth enrichment and anaerobic culture for CD. Results: Validation of the glove juice protocol showed that CD could be recovered successfully from all hand rinsate dilutions (up to 10 -6 ). When applied to farm workers, this method yielded CD in none of the hand rinsates (0%, 95% CI 0.0-92.2%). CD was also not detected in any of the human fecal samples. However, CD was detected from calf fecal samples on 10 farms (43.5%, 95% CI 20.8%-80.0%). Conclusion: While the zoonotic transmission of CD cannot be ruled out, our results suggest that contact with dairy animals is not likely to be associated with an increased risk of acquiring CD via the fecal-oral route. The glove-juice protocol appears to be a useful tool for studying the epidemiology of CD in populations where obtaining fecal samples is difficult. Disclosures: All Authors : No reported disclosures